PENERAPAN METODE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIA SD NEGERI 187 PEKANBARU - Yanti, Irma; Noviana, Eddy; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Social sciences are social sciences simplified for the purposes of education and teaching of primary and secondary schools, so that the IPS is that the social sciences are selected and adapted for use educational programs to learn other equivalent. This research is a classroom action research (PTK) which aims to improve learning outcomes IPS IIIA grade students of SD State 187 Pekanbaru. The study was conducted in two cycles, the first cycle consisted of three meetings with one test and the second cycle also consists of two cycles consist of three meetings with one daily tests. Problem in this research is the low student learning outcomes IPS , with an average grade 68.05. While the value of a minimum completeness criteria (KKM) IPS is 70. Among the students numbering 37 people only 15 students who reach KKM with 40.54% classical completeness. conducted aims to improve learning outcomes IPS IIIA grade students of SD State 187 Pekanbaru apply Examples of non Examples.Instrumen method of data collection in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of learning derived from the value of daily tests before treatment with an average of 68.05, an increase in the first cycle with the average being 76.08. In the cycle II has increased by an average of 85.54. The activities of teachers in the learning process in the first cycle of 67.85% the first meeting, a second meeting increased to 78.57% and 82.14% at the third meeting. Second cycle of the first meeting and the second meeting of the 89.28% increase to 92.85% and the third meeting is increased from the first meeting and the second 96.42%. Results of the data analysis activities of students in the first cycle of the first meeting with an average of 64.28%, the second meeting increased to 78.57% and 82.14% third meeting. The first meeting of the second cycle with the average - average 85.71%, 92.85% the second meeting and the third meeting is increased to 96.42%. Results of the study in class IIIA SDN 187 Pekanbaru prove that the application of the method of non Examples Examples can improve learning outcomes IPS IIIA grade students of SD State187 Pekanbaru.Key Words : Examples Examples the Non method, IPS Learning Results